Validity and reliability of a Portuguese version of the Summated Xerostomia Inventory‐5. (27th November 2017) - Amaral, João Pedro de Almeida Rato; Marques, Duarte Nuno da Silva; Thomson, William Murray; Vinagre, Alexandra Rosa Rodrigues; da Mata, António Duarte Sola Pereira
Abstract : Objectives: The aim of this study was to validate and determine the reliability of the Portuguese version of the Summated Xerostomia Inventory. Background: Many conditions such as head and neck radiation, autoimmune diseases or polypharmacy are characterised by hyposalivation which can affect oral and systemic quality of life. As such, this condition must be assessed, and the English version of the Xerostomia Inventory has been increasingly used to determine the severity of dry mouth perception. Materials and methods: This was a descriptive cross‐sectional study, which employed volunteers suffering from hyposalivation after local ethical committee clearance. Each patient signed an informed consent and responded to the Portuguese version of the questionnaire in the form of an interview. This was repeated again after 2 weeks. A standard single question provided a validity check. Data were analysed using Cronbach's α to test its reliability and total and interitem correlation, and intraclass correlation to determine its internal consistency and test‐retest reliability. Significance was set at .05. Results: A sample of 103 volunteers was recruited. Cronbach's α was .84 and .87 for the first and second test administrations, respectively. The intraclass correlation coefficient value for the test‐retest reliability was .93, and scores for the individual items ranged from .79 to .90. The correlation between the total score of the questionnaire and standard single dry mouth question was .66, indicating a very good correlation. Conclusion: Demonstrating excellent psychometric properties, the Summated Xerostomia Inventory (Portuguese Version) is a valid tool for quantifying Xerostomia in a dry mouth‐afflicted population.